2020
DOI: 10.1007/s10570-019-02936-6
|View full text |Cite
|
Sign up to set email alerts
|

Heteropolyacids and sulfonic acid-bifunctionalized organosilica spheres for efficient manufacture of cellulose acetate propionate with high viscosity

Abstract: The material cannot be used for any other purpose without further permission of the publisher and is for private use only. There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…Recently, Song et al. reported the functionalization of organosilica nanospheres with Brønsted acidic ILs and their subsequent impregnation with HPAs [24] . In these types of catalysts the HPA is strongly bound by ionic interaction with the imidazolium cation of the IL on the surface (Figure 11).…”
Section: Supported Hpasmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Song et al. reported the functionalization of organosilica nanospheres with Brønsted acidic ILs and their subsequent impregnation with HPAs [24] . In these types of catalysts the HPA is strongly bound by ionic interaction with the imidazolium cation of the IL on the surface (Figure 11).…”
Section: Supported Hpasmentioning
confidence: 99%
“…Recently, Song et al reported the functionalization of organosilica nanospheres with Brønsted acidic ILs and their subsequent impregnation with HPAs. [24] In these types of catalysts the HPA is strongly bound by ionic interaction with the imidazolium cation of the IL on the surface (Figure 11). The solid acid catalyst H 3 PW/Si(Et)Si-DimÀ SO 3 H (Dim = dihydroimidazole, 7.5 wt% H 3 PW loading) was successfully applied in the esterification of cellulose-to-cellulose acetate propionate.…”
Section: Silica Supportsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, POMs can exhibit good response effects in the catalysis process of reaction-controlled phase transfer. At the same time, POMs have also been confirmed as active sites for catalyzing cellulose esterifications. …”
Section: Introductionmentioning
confidence: 95%